Maternal Death Risk Factors in Wahidin Sudirohusodo Hospital and Its Affiliates: Faktor Risiko Kematian Maternal di Rumah Sakit Umum Pusat Wahidin Sudirohusodo dan Jejaringnya - Elizabet C. Jusuf; Witono Gunawan; Nurbani Bangsawan (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objectives : To identify maternal death risk factors in Wahidin Sudirohusodo Hospitals and its affiliates between 01 January - 31 December 2017 Methods: This study is an observational case control study that includes all cases of maternal death and considerable numbers of pregnancy without complications that occured in Wahidin Sudirohusodo Hospital and its affiliates between 01 January 2016 and 31 December 2017. Data were then be analysed using chi square and logistic regression test to know the correlations between risk factors and maternal death. Results :There are 28 cases of maternal death in Wahidin Sudirohusodo Hospital and its affiliates which mostly occured at age 20-35 years old (60.7%) and antenatal care in in primary health care (71,4%). Hypertension (39,3%) and hemorrhage (35,7%) were the most frequent complicaitons of maternal death. Age under 20 years old and older than 35 years old (odds ratio 3.882; 95% CI, 1.056-14.276; P<0.05), education level less than 9 years (odds ratio 3.178; 95% CI, 0.987-10.228; P<0.05), Age and education level did not seem to affect incidence of maternal death when analysed simultaneously (odds ratio 1.842; 95% CI, P> 0.05). Conclusions: Hypertension and hemorrhage were the most frequent causes of maternal death. Age under 20 years old and older than 35 years old as well as education level less than 9 yearsincreased the risk of maternal deaths independently. Parity, frequency of antenatal care, and location of antenatal care did not show any significant role in maternal death occurence. Keywords : Maternal death, risk factors, hypertension, hemorrhage, age Abstrak Tujuan: Untuk mengetahui faktor-faktor risiko kematian maternal di Rumah Sakit Umum Pusat Wahidin Sudirohusodo dan jejaringnya dalam periode 01 Januari – 31 Desember 2016. Metode : Penelitian ini penelitian studi observasional case control dengan mengambil seluruh data kematian maternal yang terjadi di Rumah Sakit Umum Pusat Wahidin Sudirohusodo dan jejaringnya dalam periode 01 Januari – 31 Desember 2016. Data dianalisis dengan Uji chi square dan regresi logistik untuk melihat faktor risiko yang diteliti dengan terjadinya kematian maternal. Hasil : Ada 28 kasus kematian maternal di Rumah Sakit Umum Wahidin Sudirohusodo dan jejarignya yang sebagian besar terjadi pada kelompok umur 20-35 tahun (60,7%) dan lokasi asuhan antenatal di Puskesmas (71,4%). Komplikasi kehamilan terbanyak ialah hipertensi (39,3%) dan perdarahan (35,7%). Kelompok umur kurang dari 20 tahun dan lebih dari 35 tahun (odds ratio 3.882; 95% CI, 1.056-14.276; P <0.05) dan pendidikan kurang dari 9 tahun (odds ratio 3.178; 95% CI, 0.987-10.228; P<0.05) memiliki pengaruh signifikan terhadap terjadinya kematian maternal . Umur dan tingkat pendidikan secara simultan tidak mempengaruhi terjadinya angka kematian maternal (odds ratio 1.842; 95% CI; P > 0.05). Kesimpulan : Hipertensi dan perdarahan merupakan penyebab utama terjadinya kematian maternal. Kelompok umur kurang dari 20 dan lebih dari 35 tahun serta tingkat pendidikan < 9 tahun secara independen berisiko meningkatkan jumlah kematian maternal. Paritas, frekuensi asuhan antenatal, dan lokasi asuhan antenatal tidak memiliki peran signifikan dalam terjadinya kematian maternal. Kata kunci : Kematian maternal, faktor risiko, hipertensi, perdarahan, umur